Kepemimpinan Kepala Sekolah Dalam Meningkatkan Profesionalisme Guru Di SMP Negeri 1 Katibung Lampung Selatan - Rezki Nopian IB (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2022)
The success of a school essentially lies in the efficiency and effectiveness of the appearance of a school principal. The approach in this study uses descriptive qualitative data collection techniques namely interviews, observation, and documentation. Then the data were analyzed using the theory developed by Males and Humberman. Research results obtained: 1) The ability of the principal to coordinate, mobilize, and harmonize all educational resources available at the school. 2) The principal directs the teacher, the principal as a leader can direct the teacher to carry out tasks in learning. 3) The principal directs and guides teachers in developing the curriculum, starting from: formulating the school's vision, mission, and goals; development of curriculum structure and content; and making school calendars. 4). The principal's ability to assist teachers in planning, implementing, and evaluating learning, preparing annual programs (Prota), semester programs (Ptomes) and syllabus.